1970
DOI: 10.1042/bj1190221
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of triglyceride synthesis and fatty acid synthesis in rat epididymal adipose tissue. Effects of altered dietary and hormonal conditions

Abstract: 1. Epididymal adipose tissues obtained from rats that had been previously starved, starved and refed a high fat diet for 72h, starved and refed bread for 144h or fed a normal diet were incubated in the presence of insulin+glucose or insulin+glucose+acetate. 2. Measurements were made of the whole-tissue concentrations of hexose phosphates, triose phosphates, glycerol 1-phosphate, 3-phosphoglycerate, 6-phosphogluconate, adenine nucleotides, acid-soluble CoA, long-chain fatty acyl-CoA, malate and citrate after 1h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
2

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 81 publications
10
50
2
Order By: Relevance
“…Although diabetic rats feeding freely con- Tables 1 and 2), confirming previous reports (2,3,18). To avoid the problems of unequal food consumption in the experiments summarized in Tables 1 and 2, all animals were fed by gastric intubation.…”
Section: Resultssupporting
confidence: 65%
“…Although diabetic rats feeding freely con- Tables 1 and 2), confirming previous reports (2,3,18). To avoid the problems of unequal food consumption in the experiments summarized in Tables 1 and 2, all animals were fed by gastric intubation.…”
Section: Resultssupporting
confidence: 65%
“…In addition, thiolase in liver cytosol does not change in activity with starvation [21]. The low activity of acetoacetyl-CoA synthetase in mammary gland and adipose tissue cytosolic fractions compared with the rates of fatty acid synthesis observed in these tissues [22,23] would also seem to preclude a major role of acetoacetyl-CoA synthetase in providing C2-units for fatty acid synthesis in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…12,24 It has been shown that leptin secretion is related to insulin-stimulated glucose uptake or metabolism in the adipocyte in vitro 11 and in vivo. 22,25 As fasting decreases the uptake and metabolism of glucose in adipose tissue, [26][27][28] this (in addition to the lower insulin responses) may be the mechanism for the lower leptin secretory response observed in the fasted rats. If leptin has a predominant role as a survival signal in response to starvation, 19 it may be important to maintain low serum leptin levels following fasting.…”
Section: Discussionmentioning
confidence: 99%